Experience with botulinum toxin in chronic migraine - A. Castrillo Sanz; N. Morollón Sánchez-Mateos; C. Simonet Hernández; B. Fernández Rodríguez; D. Cerdán Santacruz; A. Mendoza Rodríguez; M.F. Rodríguez Sanz; C. Tabernero García; P. Guerrero Becerra; M. Ferrero Ros; J. Duate García-Luis (Neurología (English Edition), 2018)
Objective: The purposes of this study were to describe our 16-month experience with onabotulinumtoxinA (OnabotA) for the treatment of chronic migraine (CM) in the Spanish province of Segovia, evaluate its benefits, and determine clinical markers of good response to treatment. Patients and methods: Prospective study of patients with CM who received OnabotA for 16 months. The effectiveness of OnabotA was evaluated based on the reduction in the number of headache days, pain intensity, and side effects. We used two-way analysis of variance to assess the effects of treatment according to the time factor. We studied the correlation between treatment effects and other variables using a linear regression model to establish the clinical markers of good response to treatment. Results: We included 69 patients who met the diagnostic criteria for CM. Patients underwent an average of two infiltrations. Mean age was 43 years; 88.4% were women. The number of headache days and pain intensity decreased significantly (P < .005); improvements remained over time. We found a negative correlation between the reduction in pain intensity and the number of treatments before OnabotA. Conclusion: The beneficial effects of OnabotA for CM continue over time. OnabotA is a safe and well-tolerated treatment whose use for refractory CM should not be delayed since early treatment provides greater benefits. Resumen: Objetivo: Describir la experiencia con la administración de toxina botulínica tipo A (OnabotA) en el tratamiento de la migraña crónica (MC) en Segovia durante 16 meses, evaluar su beneficio y buscar marcadores clínicos que sirvan para predecir una mejor respuesta al tratamiento. Pacientes y métodos: Estudio prospectivo de pacientes con MC que recibieron infiltraciones con OnabotA durante 16 meses. Se evaluó la eficacia de OnabotA comparando la reducción en el número de días de cefalea, en la intensidad y efectos adversos. Se comparó el efecto del tratamiento con el factor tiempo mediante un análisis de la varianza de dos vías (ANOVA). Se estudió la correlación del efecto del tratamiento con el resto de las variables mediante un modelo de regresión lineal para buscar marcadores clínicos que sirvan para predecir una mejor respuesta. Resultados: Se incluyó a 69 pacientes que cumplían criterios de MC. Se les realizó una media de 2 infiltraciones. La edad media fue de 43 años, el 88,4% fueron mujeres. La frecuencia de los días de cefalea y su intensidad se redujeron de forma significativa (p < 0,005) y esta mejoría se mantuvo a lo largo del tiempo. Se encontró una correlación negativa entre la reducción de la intensidad y el número de tratamientos previos a la administración de la toxina. Conclusión: El efecto beneficioso de la OnabotA en la MC se mantiene en el tiempo, siendo un tratamiento seguro y bien tolerado. No debe retrasarse su uso en MC refractaria, ya que su beneficio podría ser mayor cuanto antes se administre. Keywords: Chronic migraine, OnabotulinumtoxinA, Prospective study, Palabras clave: Migraña crónica, Toxina botulínica A, Estudio prospectivo